A SCIENTIFIC OVERVIEW OF COMBINATORICS AND PROBABILITY CALCULATION ELEMENTS - Tilavov Fazliddin Shokir ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Combinatorics is a significant part of mathematics that studies the systematic numbering, arrangement, and organization of items. This article gives a thorough review of the fundamentals of combinatorics and its applications in probability calculations. Fundamental topics including permutations, combinations, probability computation, the multiplication principle, and binomial coefficients are thoroughly studied. The purpose of this article is to explain the importance of combinatorial approaches in solving probability and counting issues, with implications for a variety of scientific and mathematical fields.